Influence Of Perceived Social Support On Career Decision -Making Self Efficacy Among Undergraduate Students - et. al., Jonah Angeline , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A career is an inevitable part of everyone's life. There are wide ranges of careers available. Choosing the right career is crucial for the students. A proper career may give job satisfaction and higher quality of life. Same way wrong career may give frustration and disappointment. Choosing the right career during the adolescent period is very important. Social support enhances self-efficacy and motivation. This study is administered with 50 male undergraduate students and 50 female undergraduate students to check whether social support influences career decision-making self-efficacy. The result shows that there is a positive correlation between social support and career decision-making self-efficacy and female students have more perceived social support than male students.